2022
DOI: 10.4236/ajps.2022.137068
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Methane Mitigation Efficacy Using <i>Asparagopsis</i>-Derived Bioactives Stabilized in Edible Oil Compared to Freeze-Dried <i>Asparagopsis in Vitro</i>

Abstract: Asparagopsis oil products are of interest due to the stabilizing effects of the Asparagopsis-derived antimethanogenic bioactive compound bromoform (CHBr 3 ). The objective of this in vitro series is to characterize antimethanogenic efficacy of freeze-dried Asparagopsis (FD-Asp) and Asparagopsis oil (Asp-Oil) and compare relative antimethanogenic response over time at multiple levels of CHBr 3 delivery. Relative methane (CH 4 ) emissions (mL/g) are based on in vitro apparent feed digested dry matter (IVDDM) aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Additionally, the use of a lipid source in feed mixtures is already implemented as an approach for methane mitigation in ruminants making it a practical candidate to deliver bromoform (Beauchemin et al 2007). The effectiveness of bromoform in oil for methane mitigation in vitro has been demonstrated recently by Kinley et al (2022). Animal trials using Asp-Oil are in progress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the use of a lipid source in feed mixtures is already implemented as an approach for methane mitigation in ruminants making it a practical candidate to deliver bromoform (Beauchemin et al 2007). The effectiveness of bromoform in oil for methane mitigation in vitro has been demonstrated recently by Kinley et al (2022). Animal trials using Asp-Oil are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Magnusson et al (2020) has shown that when fresh harvested Asparagopsis is immersed and homogenized into edible oils (Asp-Oil), there is a transfer and stabilization of bromoform. Furthermore, Asp-Oil has been shown to be as effective as FD-Asp at methane mitigation in vitro (Kinley et al 2022). While continuous improvements toward Asparagopsis derived bromoform conservation are being made, it is also important to understand the retention of bromoform within FD-Asp and Asp-Oil which will ultimately be used to identify their respective shelf-life for on farm use.…”
Section: Introductionmentioning
confidence: 99%